Analisis Faktor-Faktor Pembentuk Kepuasan Pelanggan Hotel : (Studi Pada Hotel Amboina Kota Ambon) - Roy Alan Wattimena (P3M Politeknik Negeri Ambon, 2023)
Currently, competition is increasingly fierce, requiring business people to be able to maximize their company's performance in order to compete in the market. Companies must strive to learn and understand the needs and wants of their customers. In particular, the company's hotel business must have value in the eyes of customers and good management so that goals can be carried out effectively and efficiently. The purpose of this study was to test and analyze the effect of service quality on customer satisfaction at the Amboina Ambon hotel.The analysis used uses simple linear regression, the population of this study is users who use the services of the Amboina Hotel and the sample used is 100 peopleThe results of this study indicate that service quality has a positive and significant effect on customer satisfaction at the Amboina hotel. Hotel Amboina should pay more attention to and improve the quality of service to meet the needs of hotel guests. Keywords: Forming Factors of Customer satisfaction